2004
DOI: 10.1023/b:neon.0000040820.78643.0a
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation After Surgically Induced Brain Injury in the Rat: Timing in Relation to Severity of Radiation Damage

Abstract: The aim of this study was to evaluate how timing of irradiation after brain surgery in rats relates to overall extent of brain radiation damage. Extent of injury was determined according to lipid peroxidation (malondialdehyde; MDA) levels in brain tissue. Thirty female rats were randomly assigned to five equal groups (Groups A-E). Four groups underwent trephination and scalpel hemisection of right frontal lobe. Rats in Groups B and D received 25 Gy cranial irradiation in a LINAC system at 10 and 20 days after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…Peker et al compared the MDA levels in the brain in the rats that underwent irradiation in a single fraction of 25 Gy either at 10 days or at 20 days following brain surgery consisting of right frontal lobe hemisection in comparison to the rats that underwent sham irradiation following sham brain surgery in a study evaluating the timing of irradiation following brain surgery. At 24 h following irradiation or sham irradiation, the rats that underwent irradiation at 10 days following brain surgery and the rats that underwent irradiation at 20 days following brain surgery had significantly increased mean MDA levels as compared to the rats that underwent sham irradiation following sham brain surgery [21]. In a study evaluating melatonin as a protectant against the oxidant injury induced by irradiation, Bhatia and Manda compared the GSHPX activities in the brain in the mice that underwent irradiation in a single fraction of 6 Gy in comparison to the mice that underwent sham irradiation.…”
Section: Discussionmentioning
confidence: 92%
“…Peker et al compared the MDA levels in the brain in the rats that underwent irradiation in a single fraction of 25 Gy either at 10 days or at 20 days following brain surgery consisting of right frontal lobe hemisection in comparison to the rats that underwent sham irradiation following sham brain surgery in a study evaluating the timing of irradiation following brain surgery. At 24 h following irradiation or sham irradiation, the rats that underwent irradiation at 10 days following brain surgery and the rats that underwent irradiation at 20 days following brain surgery had significantly increased mean MDA levels as compared to the rats that underwent sham irradiation following sham brain surgery [21]. In a study evaluating melatonin as a protectant against the oxidant injury induced by irradiation, Bhatia and Manda compared the GSHPX activities in the brain in the mice that underwent irradiation in a single fraction of 6 Gy in comparison to the mice that underwent sham irradiation.…”
Section: Discussionmentioning
confidence: 92%
“…18 Rat model studies have demonstrated higher levels of brain injury with early initiation of radiation. 19 …”
Section: Discussionmentioning
confidence: 99%
“…If similar trends are corroborated in post-hoc analyses of patients who were treated by irradiation combined with temozolomide then consideration should be given to a trial design that compares moderate-length intervals between surgery and irradiation to earlier initiation of treatment (e.g., 5 vs. 2 weeks). The biological rationale for this concept is available [51], but does the equipoise exist to mount such an effort? Fig.…”
Section: Discussionmentioning
confidence: 99%